2019
DOI: 10.1007/s40430-019-2102-3
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of the polanga biodiesel blends during the application to the diesel engine performance and emission parameters—Taguchi and RSM approach

Abstract: The excessive use of fossil fuels has caused a rapid increase in air pollution all over the world. This alarming situation demands that environment-friendly fuels and their performance must be investigated for the diesel engine. The present study investigates a CI engine fueled with polanga biodiesel for the optimum performance and emission parameters. This study also tries to optimize the input parameters in order to achieve the corresponding optimized engine performance. In the present work, various input pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Results from experimental runs of the TCP engine with COME25 at 10%, 20%, and 30% EGR revealed that the improved feature worked as expected. The standard HCP engine's increased swirl movement and turbulence within the cylinder led to a significant reduction in NOx emissions; however, the BTE of COME25 with the TCP engine is only 29.12% with 20% EGR, and it's only 29.58% without EGR at peak load [7][8][9][10] . Improvements in CO and HC were seen for COME25 when EGR rates were raised throughout the test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from experimental runs of the TCP engine with COME25 at 10%, 20%, and 30% EGR revealed that the improved feature worked as expected. The standard HCP engine's increased swirl movement and turbulence within the cylinder led to a significant reduction in NOx emissions; however, the BTE of COME25 with the TCP engine is only 29.12% with 20% EGR, and it's only 29.58% without EGR at peak load [7][8][9][10] . Improvements in CO and HC were seen for COME25 when EGR rates were raised throughout the test.…”
Section: Discussionmentioning
confidence: 99%
“…Due to rising energy needs and worries about the depletion of fossil fuel supplies, the study of biodiesel's combustion characteristics becomes paramount 8 . If biodiesel powered diesel engines can be optimized to match or exceed the performance of their fossil fuel counterparts, it would represent a significant step toward a more sustainable energy future.…”
Section: Energy Sustainabilitymentioning
confidence: 99%
“…Provided data from RFID is strongly dependent on environmental conditions (Choudhary et al, 2019).The evaluation of water levels in soil have been done using two existing methods by Sergio Francisco Pichorim et al They evaluated double tags and SL900A PCB process (Pichorim et al, 2018). Choudhary et al plotted the main effect of received signal strength for LTE (RSSSLTE) technology by using MIMITAB17 software including relative humidity and air quality as main accounting parameters in variable temperature of atmosphere (Choudhary et al, 2020).Sharma et al optimized engine input parameters by using dual optimization technique Taguchi and RSM (Sharma et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…In this regard, the use of nanoparticles blended in diesel/biodiesel is a potential domain that can meet the expectations of researchers. 1,2 The first five articles of this special issue focus on the use of nanoparticles and their effects on important parameters of diesel engines. The first article by Kumar et al 3 investigates the effects of different blends of waste plastic oil in CID diesel engines for different injection timings.…”
mentioning
confidence: 99%